1993
DOI: 10.1007/bf03348828
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutical doses of salbutamol inhibit the somatotropic responsiveness to growth hormone-releasing hormone in asthmatic children

Abstract: In humans beta-adrenergic receptors mediate an inhibitory effect on somatotropic function, likely via stimulation of hypothalamic somatostatin release. Accordingly, salbutamol (SAL), a beta 2-agonist, given iv abolishes the GH response to GH-releasing hormone (GHRH) in adults. Taking into account that in bronchial asthma an alteration in the beta-adrenergic neural control of airways has been hypothesized, we aimed to verify whether, in asthmatic children, beta-adrenergic activation inhibits or not GH secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To our knowledge, the pharmacological properties of caffeine regarding GH response have not been considered and previous data on the effects of acute salbutamol on GH are quite limited [9 -11]. Studies in experimental animals or in humans have found acute salbutamol administration either to decrease [9] GH secretion, probably due to enhanced somatostatin secretion and/or activity, or not to have any effect on GH secretion [11]. In the single exercise study in adult patients with asthmatic bronchitis, Giustina et al [10] found that acute b 2 stimulation blunts Physiology & Biochemistry the physiological GH response to maximal exercise.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the pharmacological properties of caffeine regarding GH response have not been considered and previous data on the effects of acute salbutamol on GH are quite limited [9 -11]. Studies in experimental animals or in humans have found acute salbutamol administration either to decrease [9] GH secretion, probably due to enhanced somatostatin secretion and/or activity, or not to have any effect on GH secretion [11]. In the single exercise study in adult patients with asthmatic bronchitis, Giustina et al [10] found that acute b 2 stimulation blunts Physiology & Biochemistry the physiological GH response to maximal exercise.…”
Section: Discussionmentioning
confidence: 99%
“…11 The evaluation, which utilizes the ratio with creatinine, does not offer any advantage over the expression of U-GH excretion as nanogram per night 11 ; therefore, we did not use this method. The impact of any adverse effect of inhaled beta-2 agonist on GH excretion 23,24 in this study is minimized by the fact that all the participants used an inhaled beta-2 agonist only once per week or not at all. We assume, therefore, that the net exogenous effects on the excretion of GH in these children were the results of inhaled medications taken regularly, namely, ICS or CrS.…”
Section: Discussionmentioning
confidence: 98%
“…25 Those authors did not take into consideration the amount of the administered beta-2 agonist. Since it is known that a beta-2 agonist can cause an inhibition of GH secretion, 23,24 the net result of GH secretion will be influenced by the opposite effects of CrS and beta-2 agonist. Therefore, the normal levels of U-GH which were found in the CrS-treated group in their study might be explained by an inhibitory effect of the beta-2 agonist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, non-steroid asthma treatments (e.g. b 2 -receptor activation) may also inhibit the GH axis (37). Several recent studies have utilized knemometry, a sensitive technique of measuring growth of the lower leg, to assess short-term effects of higher dose IC therapy on growth.…”
Section: Do Inhaled Corticosteroids Impair Linear Growth?mentioning
confidence: 99%